Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Literasi Sains Pada Materi Pencemaran Lingkungan - Mudumi, Sahfitri; Irianti, Mustika; Kumalasari, Lina (UNIB Press, 2024)
The application of teaching materials and teaching resources in learning is appropriate and needs to be paid attention to. The research carried out aims to develop a student worksheet (LKPD) based on scientific literacy on the sub-material of environmental pollution with the topic of water pollution which can increase students' understanding of environmental pollution. This research uses research and development (R&D) methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). LKPD testing was carried out at SMP Negeri 01 Raja Ampat in grade seven involving 12 students. Based on the research findings, data analysis was carried out with results of 96.43% from material experts and 85.83% from media experts and fulfilling the very feasible category. For the regarding the results of the effectiveness test, student learning outcomes were found to be in the high category with a value of n ≥ 0.7. Meanwhile, the results of the practicality test through student responses showed that 12 students were positively interested in using LKPD in terms of scientific knowledge with a percentage result of 95%. Therefore, it can be concluded that LKPD can be used in learning.